UBIQUITOUS LOW-FEO RELICT GRAINS IN TYPE II CHONDRULES AND LIMITED OVERGROWTHS ON PHENOCRYSTS FOLLOWING THE FINAL MELTING EVENT - Wasson J.T.; Rubin A.E. (My University, 2003)
Type II porphyritic chondrules commonly contain several large (>40 μm) olivine phenocrysts; furnace-based cooling rates based on the assumption that these phenocrysts grew in a single-stage melting-cooling event yield chondrule cooling-rate estimates of 0.01-1 K s-1. Because other evidence indicates much higher cooling rates, we examined type II chondrules in the CO3.0 chondrites that have experienced only minimal parent-body alteration. We discovered three kinds of evidence indicating that only minor (4-10 μm) olivine growth occurred after the final melting event: (1) Nearly all (>90%) type II chondrules in CO3.0 chondrites contain low-FeO relict grains; overgrowths on these relicts are narrow, in the range of 2-12 μm. (2) Most type II chondrules contain some FeO-rich olivine grains with decurved surfaces and acute angles between faces indicating that the grains are fragments from an earlier generation of chondrules; the limited overgrowth thicknesses following the last melting event are too thin to disguise the shard-like nature of these grains. (3) Most type II chondrules contain many small (<20 μm) euhedral or subhedral phenocrysts with central compositions that are much more ferroan than the centers of large phenocrysts; their small sizes document amount growth occurred after final melting event. if overgrowth thicknesses were (4-10 event, it follows fractions coarse (>40 μm) high-FeO phenocrysts are relicts from earlier generations of chondrules, and that cooling rates after the last melting event were much more rapid than indicated by models based on a single melting event. These observations are thus inconsistent with the ''classic'' igneous model of formation of type II porphyritic chondrules by near-total melting of a precursor mix followed by olivine nucleation on a very limited number of nuclei (say, =<10) and by growth to produce the large phenocrysts during a period of monotonic (and roughly linear) cooling. Our observations that recycled chondrule materials constitute a large component of the phenocrysts of type II chondrules also imply that this kind of chondrule formed relatively late during the chondrule-forming period.